An Anthropometric Comparison of Inner Canthal Distance, Outer Canthal Distance and Canthal Index in the Indian and Nepalese Undergraduate Students of Nepalgunj Medical College - Adhikari, N; Ambekar, M N; KC, S (Journal of Nepalgunj Medical College, 2018)
Background: The canthal distances are one of the most important aspects in ascessing the facial aesthetics. Several authors have described changes in the canthal distances attributable to race and gender. Aims and Objectives: To compare the inner canntahl distance, outer canthal distance and canthal index in between Nepalese and Indian undergraduate students of Nepalgunj Medical College. Materials and Methods: The study was conducted to compare canthal distances and canthal index among 320 (160 Indians: 100 male,60 female and 160 Nepalese: 100 male and 60 female) undergraduate students of Nepalgunj Medical College of age group 18-24 years at Department of Anatomy, Chisapani, Banke. Inner canthal distance(ICD) and Outer canthal Distance(OCD) were measured by using round end spreading caliper and Canthal Index were calculated by ICD/OCD *100. The value obtained was compared among Indian and Nepalese students in both sexes by using student t-test. Result: The study showed that there was no any significant difference on the value of inner and outer canthal distances and canthal index observed between Nepalese and Indian population except on the value of canthal index which was significantly different between Indian male and Nepalese male population. However, when the comparison was done between the sexes, inner and outer canthal distances and canthal index of males are larger than females except on the value of canthal index of Indian males and Indian females which was non-significant. Conclusion: There occurred a sexual dimorphism within Indian and Nepalese population except on canthal index of Indian male and Indian female but there wasn’t any significant differences between Nepalese and Indian population of same sex except on canthal index of Indian male and Nepalese male. JNGMC, Vol. 14 No. 2 December 2016, Page: 12-14